Urban-Rural Differences in The Association Between Physical Activity and Overweight/Obesity Among Indonesian Adolescents: A Cross-Sectional Study - Wulandari, Wahyu; M. Irzal, Mufti As Siddiq; Fatmawati, Lady Farah (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Adolescent overweight/obesity is an increasing public health concern and contributes to the risk of non-communicable diseases later in life. Physical activity plays an important role in weight regulation. However, its association with overweight/obesity may vary according to residential setting. This study aimed to examine the association between physical activity and overweight/obesity among adolescents living in rural and urban areas of Indonesia. A cross-sectional study was conducted using data from the 2023 Indonesian Health Survey. The study included 115,372 adolescents aged 10–18 years. Physical activity was classified based on total Metabolic Equivalent of Task (MET)-minutes per week (≥600 MET-minutes/week), while nutritional status was assessed using body mass index-for-age Z-scores. Complex samples logistic regression analyses were performed separately for rural and urban adolescents, adjusting for sex, unhealthy food consumption, and parental metabolic syndrome risk factors. The prevalence of overweight/obesity was higher among urban than rural adolescents. Adolescents with insufficient physical activity had higher odds of overweight/obesity in both settings. After adjustment, insufficient physical activity remained significantly associated with overweight/obesity among rural adolescents (aOR:1.29;95%CI:1.04–1.61), whereas the association was not statistically significant among urban adolescents (aOR:1.13;95%CI:0.98–1.29). The association between physical activity and overweight/obesity differed according by residential setting. Insufficient physical activity was associated with overweight/obesity among rural but not urban adolescents. These findings highlight the importance of considering rural–urban differences when developing adolescent overweight/obesity prevention strategies in Indonesia. Keywords: Adolescents, Physical Activity, Overweight/Obesity, Urban-Rural Differences